2005
DOI: 10.1111/j.1365-2222.2005.02391.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae infection enhances cellular proliferation and reduces steroid responsiveness of human peripheral blood mononuclear cells via a tumor necrosis factor‐α‐dependent pathway

Abstract: C. pneumoniae infection enhanced the proliferation and survival of immune and inflammatory cells, resulting in steroid resistance. The reversal of these phenomena by the TNF-alpha inhibitor suggests that TNF-alpha may play an important role in the induction of steroid dependence or resistance. A TNF-alpha inhibitor may therefore be a candidate agent for managing steroid-dependent or -resistant severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 22 publications
1
29
0
1
Order By: Relevance
“…We have also shown that C. pneumoniae infection induces corticosteroid resistance, since the survival of C. pneumoniae-infected immune cells in response to dexamethasone treatment is enhanced (Cho et al, 2005). Recently, it has been suggested that GRb is a dominant-negative inhibitor of GRa-mediated transactivation of target genes, and that it promotes GC resistance by altering transcription at GC-inducible, AP-1 inducible or NFkB-inducible promoters (Pujols et al, 2004(Pujols et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also shown that C. pneumoniae infection induces corticosteroid resistance, since the survival of C. pneumoniae-infected immune cells in response to dexamethasone treatment is enhanced (Cho et al, 2005). Recently, it has been suggested that GRb is a dominant-negative inhibitor of GRa-mediated transactivation of target genes, and that it promotes GC resistance by altering transcription at GC-inducible, AP-1 inducible or NFkB-inducible promoters (Pujols et al, 2004(Pujols et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…C. pneumoniae was cultured and prepared as previously described (Cho et al, 2005;Park et al, 2010). In brief, strain TW183 was purchased from the American Type Culture Collection (ATCC, Manassas, VA, USA) and propagated in HEp-2 cells (ATCC) grown in Eagle's minimum essential medium (Sigma) supplemented with 10 % fetal calf serum, L-glutamine (2 mM), non-essential amino acids, gentamicin (10 mg l Infected cells were cultured in a 35 uC, 5 % CO 2 saturated humidified incubator, harvested on day 3 or 4, and disrupted by two cycles of freezing/thawing and ultrasonication; similar harvests were pooled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroid treatment also promotes chlamydial infection in vitro and reactivates persistent lung infection in vivo (53,54), and asthmatic patients on high, as opposed to low, doses of inhaled steroids are more likely to have evidence of Chlamydophila pneumoniae infection (55). Most importantly, asthmatics with evidence of infection are more resistant to steroid treatment than are asthmatics without infection (56). These observations suggest that treatment may result in increased susceptibility to acute infection or reactivation of persistent chlamydial lung infection and that infection induces a phenotype of asthma that is more resistant to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…That W. pipientis had the ability to modify in vitro growth characteristics of the Aa23 cells possibly through enhancement of granulin signalling or up-regulation of the unknown regulatory molecules is intriguing and worthy of further study. It has been shown that intracellular infection of cells by viruses or bacteria may result in an up-regulation proliferation in infected cells via various mechanisms such as induction of mitogenactivated protein kinase signalling pathways, or the upregulation of secreted and cell surface molecules that affect proliferation (Cho et al, 2005;Zhao et al, 2007). Recombinant goldfish granulin induced the proliferative response in M. sexta primary haemocytes that was further evidence supporting the observations that the proliferative effect observed in Aa23 cells was not a result of the presence of W. pipientis or the treatment performed to remove it, and that granulin's ability to induce proliferation is conserved.…”
Section: Discussionmentioning
confidence: 99%